2017
DOI: 10.3892/ol.2017.7524
|View full text |Cite
|
Sign up to set email alerts
|

MiR‑370 promotes apoptosis in colon cancer by directly targeting MDM4

Abstract: MicroRNA (miR)-370 functions as a tumor suppressor or promoter in several cancers. However, the expression and biological role of miR-370 in colon cancer remains undefined. In the present study, miR-370 expression in both normal and malignant colon tissues was quantified by quantitative polymerase chain reaction. An in vitro cell viability and apoptosis assay and an in vitro xenograft tumor model were employed to investigate the role of miR-370 on colon cancer growth. Furthermore, the potential direct target o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
(25 reference statements)
3
17
0
Order By: Relevance
“…The previous study has demonstrated the role of miR-370 in inhibiting proliferation and inducing apoptosis in CRC cells. 25 Here, we focused on the effect of miR-370-3p on the proliferation and EMT of colon cancer cells. HCT116 and SW620 cells with the lowest expression of miR-370 25 were selected for this study.…”
Section: Mir-370-3p Suppresses Proliferation and Emt Of Colon Cancer mentioning
confidence: 99%
See 3 more Smart Citations
“…The previous study has demonstrated the role of miR-370 in inhibiting proliferation and inducing apoptosis in CRC cells. 25 Here, we focused on the effect of miR-370-3p on the proliferation and EMT of colon cancer cells. HCT116 and SW620 cells with the lowest expression of miR-370 25 were selected for this study.…”
Section: Mir-370-3p Suppresses Proliferation and Emt Of Colon Cancer mentioning
confidence: 99%
“…25 Here, we focused on the effect of miR-370-3p on the proliferation and EMT of colon cancer cells. HCT116 and SW620 cells with the lowest expression of miR-370 25 were selected for this study. The regulatory effect of miR-370-3p on the proliferation of HCT116 cells and SW620 cells was evaluated by using CCK-8 assay.…”
Section: Mir-370-3p Suppresses Proliferation and Emt Of Colon Cancer mentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement, MDM4 gene has been detected in about 50% of CRC patients and plays an important negative regulator role of p53 [ 35 ]. In CRC patients, MDM4 is regulated by several factors [ 36 ] and represents a target of miR-370 [ 37 ]. Regarding THBD gene, it encodes for thrombomodulinand which is resulted hypermethylated in early-stage CRC [ 38 ].…”
Section: Discussionmentioning
confidence: 99%